Transformation of Green Areas in Central Squares after Revitalization: Evidence from Cittaslow Towns in Northeast Poland - Agnieszka Jaszczak; Ewelina Pochodyła; Beata Płoszaj-Witkowska (Land, 2022)
In recent years, unfavorable changes in the development of city squares can be observed in Poland due to poorly conducted revitalization. These changes include, among others, the elimination of greenery or its significant reduction and the introduction of impervious surfaces to the places formerly designated by forms of greenery. This article highlights the need to redesign the central squares in small towns as part of their revitalization, including three levels of approach: functional, ecological, and aesthetic. The research aimed to analyze the degree of changes in the development of green areas in central squares due to the implementation of revitalization projects. Central squares in four selected towns of Cittaslow from the Warmia and Mazury region (northeastern Poland) were selected as the research area. The methods of comparative analysis were used, considering the comparison of functions, space, and composition, as well as the “research by design” method, which was adopted. A comparative analysis of changes in the arrangement of squares and analysis of changes in greenery structure was performed. The results showed that, in two examples, the changes related to removing greenery from the squares were not on a large scale due to the compensation with new forms. However, the vegetation was removed in two squares without introducing new forms or compensating for the greenery to a minimum extent. This allowed us to answer whether the structure and various forms submitted in the greenery projects in the squares, so-called landscape architecture objects, correspond to the current ecological design requirements. From the perspective of landscape architecture and ecological design, it was positive to introduce a diversified vegetation structure and supplement it with medium and tall forms, as evidenced by the development of the square in Biskupiec. However, the results also showed a negative aspect of the revitalization conducted by removing the greenery and replacing it with an impermeable surface, for example, in the square in Bartoszyce. The final stage was to propose general guidelines for revitalizing squares and design proposals considering introducing plant forms in the squares in the four analyzed towns.